PKM NELAYAN TANGKAP DUSUN LUPUS - Erwin Tanjaya; R M K Teniwut (Ngayah: Majalah Aplikasi IPTEKS, 2019)
Fishing fishery is one of of adverise sectors mainly in the Coastal area, including in this case fishermen in Lupus Sub Village - Labetawi Village, Tual City, Maluku Province. Fishing fishery is one of adverise sectors mainly in the Coastal area, including in this case fishermen in Lupus Village - Labetawi Village, Tual City, Maluku Province. Lupus has rich potential in fish resources (SDI) where the demersal fish species that have high economic value such as; fish Grouper, Cockatoo, Red Fish, Jackfruit Seeds, and Yellow Tail Fish are the types of fish that are often targeted by fishermen using fishing gear and traps.Two fishing gears have been use fisherman this community service is also to find other types of fishing equipment that are consuder productive catches. The partner, in this case, is a fisherman who is a reliable fishermen in the field of fishing, but they are still depend on the owner's fishermen. The fishing facilities that used in getting the catch must be partially paid to the owner's fishermen. The purpose of this community service program is to make both partners become entrepreneurs who are able to manage their own fishing business and not depend on other owners so that they can help to improve the economic level of both partners through effective fishing fisheries management.